Label-free detection of anti-estrogen receptor alpha and its binding with estrogen receptor peptide alpha by terahertz spectroscopy. Issue 39 (4th May 2017) - Li, Mingliang; Chang, Tianying; Wei, Dongshan; Tang, Mingjie; Yan, Shihan; Du, Chunlei; Cui, Hong-Liang
Abstract : Terahertz (THz) spectroscopic techniques were employed to study the hydration shell formation around anti-estrogen receptor alpha (AER-α) and to detect the binding reaction between AER-α and estrogen receptor peptide alpha (ERP-α). Abstract : Terahertz (THz) spectroscopic techniques were employed to study the hydration shell formation around anti-estrogen receptor alpha (AER-α), an important biomarker in breast cancer diagnosis, and to detect the binding reaction between AER-α and estrogen receptor peptide alpha (ERP-α), in aqueous solutions. A remarkable nonlinear relation between THz absorption and AER-α concentration was demonstrated, shedding some light on the formation process of the hydration shell around AER-α. THz spectroscopic properties of the AER-α were also shown to be significantly affected by the binding with the ERP-α, to the extent that THz transmission and attenuation could be used to investigate the dielectric properties of antibody–antigen binding reactions.